The Relationship between Strategic Change Management and Operational Effectiveness of World-Class Standard Schools: The Moderating, Creative Leadership - Phumsuwan, Pansakan; Lalaeng, Chanyaphak (Journal of Posthumanism, 2025)
This research aims to check the consistency and develop a model. It also explores The Relationship between Strategic Change Management and Operational Effectiveness of World-Class Standard Schools. The population used in this study was 593 school administrators of international standard schools that received the OBECQA Quality Award, a sample of 250. Using the Smart PLS model, a two-stage approach was used for direct path, mediation and mediation effect analysis with high-dimensional latent variables. The results of the study found that SCM has direct positive effect on CSVC and OE. In addition CSVC has direct positive effect on OE. The results of the mediation influence test found that, SMC impact OE through the mediation of CSVC. In addition, found that, SCM no impact CSVC through the moderator of CL. However, SCM impact OE through the moderator of CL.